The Epigenetic Regulation in Plant Specialized Metabolism: DNA Methylation Limits Paclitaxel in vitro Biotechnological Production - Escrich, Ainoa; Cusido, Rosa M.; Bonfill, Mercedes; Palazon, Javier; Sanchez-Muñoz, Raul; Moyano, Elisabeth (Frontiers in Plant Science, 2022)
Environmental conditions are key factors in the modulation of the epigenetic mechanisms regulating gene expression in plants. Specifically, the maintenance of cell cultures in optimal in vitro conditions alters methylation patterns and, consequently, their genetic transcription and metabolism. Taxol® production in Taxus x media cell cultures is reduced during its maintenance in in vitro conditions, compromising the biotechnological production of this valuable anticancer agent. To understand how DNA methylation influences taxane production, the promoters of three genes (GGPPS, TXS, and DBTNBT) involved in taxane biosynthesis have been studied, comparing the methylation patterns between a new line and one of approximately 14 years old. Our work revealed that while the central promoter of the GGPPS gene is protected from cytosine methylation accumulation, TXS and DBTNBT promoters accumulate methylation at different levels. The DBTNBT promoter of the old line is the most affected, showing a 200 bp regulatory region where all the cytosines were methylated. This evidence the existence of specific epigenetic regulatory mechanisms affecting the last steps of the pathway, such as the DBTNBT promoter. Interestingly, the GGPPS promoter, a regulatory sequence of a non-specific taxane biosynthetic gene, was not affected by this mechanism. In addition, the relationship between the detected methylation points and the predicted transcription factor binding sites (TFBS) showed that the action of TFs would be compromised in the old line, giving a further explanation for the production reduction in in vitro cell cultures. This knowledge could help in designing novel strategies to enhance the biotechnological production of taxanes over time.